The evolutionary adaptation of the C282Y mutation to culture and climate during the European Neolithic. Issue 1 (22nd January 2016) - Heath, Kathleen M.; Axton, Jacob H.; McCullough, John M.; Harris, Nathan
ABSTRACT: Objectives: The C282Y allele is the major cause of hemochromatosis as a result of excessive iron absorption. The mutation arose in continental Europe no earlier than 6, 000 years ago, coinciding with the arrival of the Neolithic agricultural revolution. Here we hypothesize that this new Neolithic diet, which originated in the sunny warm and dry climates of the Middle East, was carried by migrating farmers into the chilly and damp environments of Europe where iron is a critical micronutrient for effective thermoregulation. We argue that the C282Y allele was an adaptation to this novel environment. Materials and Methods: To address our hypothesis, we compiled C282Y allele frequencies, known Neolithic sites in Europe and climatic data on temperature and rainfall for statistical analysis. Results: Our findings indicate that the geographic cline for C282Y frequency in Europe increases as average temperatures decrease below 16°C, a critical threshold for thermoregulation, with rainy days intensifying the trend. Discussion: The results indicate that the deleterious C282Y allele, responsible for most cases of hemochromatosis, may have evolved as a selective advantage to culture and climate during the European Neolithic. Am J Phys Anthropol 160:86–101, 2016. © 2016 The Authors American Journal of Physical Anthropology Published by Wiley Periodicals, Inc.